2015
DOI: 10.1002/humu.22909
|View full text |Cite
|
Sign up to set email alerts
|

Putative Prostate Cancer Risk SNP in an Androgen Receptor‐Binding Site of the Melanophilin Gene Illustrates Enrichment of Risk SNPs in Androgen Receptor Target Sites

Abstract: Genome-wide association studies have identified genomic loci, whose single nucleotide polymorphisms (SNPs) predispose to prostate cancer (PCa). However, the mechanisms of most of these variants are largely unknown. We integrated chromatin-IP coupled sequencing and microarray expression profiling in TMPRSS2-ERG gene rearrangement positive DUCaP cells with the GWAS PCa risk SNPs catalog to identify disease susceptibility SNPs localized within functional androgen receptor binding sites (ARBSs). Among the 48 GWAS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 75 publications
(124 reference statements)
4
27
0
Order By: Relevance
“…Specifically, the regulation has been observed to be SRF‐dependent, which relates to less than 6% of androgen‐regulated genes (Heemers et al, ). Interestingly, androgen treatment results in lower levels of DGAT2 (Ngan et al, ; Heemers et al, ; Rajan et al, ; Bu et al, ), which is similar to our finding of the association of the PrCa death‐associated alleles on the gene expression. Even though no AR binding cite exists on the location of the SNPs studied here (Lin et al, ; Massie et al, ), the effect of androgens could be mediated through an AR cooperator binding which the SNPs regulate.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Specifically, the regulation has been observed to be SRF‐dependent, which relates to less than 6% of androgen‐regulated genes (Heemers et al, ). Interestingly, androgen treatment results in lower levels of DGAT2 (Ngan et al, ; Heemers et al, ; Rajan et al, ; Bu et al, ), which is similar to our finding of the association of the PrCa death‐associated alleles on the gene expression. Even though no AR binding cite exists on the location of the SNPs studied here (Lin et al, ; Massie et al, ), the effect of androgens could be mediated through an AR cooperator binding which the SNPs regulate.…”
Section: Discussionsupporting
confidence: 91%
“…The SNPs were not observed to affect the expression of DGAT2 in prostate tissue based on GTEx Portal, which further supports the role of DGAT2 in the later stage of malignant transformation rather than in the initiation of tumor development. Previously, DGAT2 has been identified in androgen-related studies as being an androgenregulated gene in PrCa cell lines (Lin et al, 2009;Ngan et al, 2009;Heemers et al, 2011;Rajan et al, 2011;Bu et al, 2016) and having an androgen receptor (AR) binding cite (Massie et al, 2011;Bu et al, 2016). Specifically, the regulation has been observed to be SRF-dependent, which relates to less than 6% of androgen-regulated genes (Heemers et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Publicly available androgen receptor ChIP-Seq data from public datasets (GSE62442, GSE65478, and GSE70679; refs. 29,30) were analyzed in the UCSC browser. Detailed analysis was performed by calculating the coverage of aligned reads on 50-bp windows using bedtools (31).…”
Section: Analysis Of Public Bisulfite-seq and Androgen Receptor Chip-mentioning
confidence: 99%
“…Furthermore, inhibition of androgen receptor by enzalutamide was able to increase SOCS3 expression approximately 3-to 4-fold in the presence of different IL6 concentrations. To further investigate the mechanism of SOCS3 regulation by the androgen receptor, we screened for androgen receptor-binding sites in the SOCS3 gene using 12 published ChIP-Seq datasets (29,30). No androgen receptor-binding element could be found in the vicinity of the transcription start site of SOCS3 ( Supplementary Fig.…”
Section: Socs3 Is Expressed In Androgen Receptor-positive Prostate Camentioning
confidence: 99%
“…Moreover, a detailed investigation of AR-binding sites identified in the LNCaP-AR dataset revealed that most of these sites are predicted to contain ARE motifs. (Stelloo et al 2015, Bu et al 2016 (Supplementary Fig. 5).…”
Section: Ar Is a Direct Regulator Of Prkd1 Expressionmentioning
confidence: 99%